High-thermal-conductivity self-lubricating titanium alloy for sliding bearing and preparation method thereof
By depositing the coating on the surface of TiAl alloy and induced in situ reactions using a high-energy laser beam, a combination of self-lubricating and high thermal conductivity is solved, and the problem of serious wear in high-temperature environments is achieved, and higher wear resistance is achieved and thermal conductivity.
Patent Information
- Application Number
- CN202411482360.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional sliding bearings are difficult to ensure high stiffness, high strength and wear resistance in high temperature environments, mainly due to wear and failure caused by poor lubricity.
By depositing TiAlC and TiAlN coatings on the surface of TiAl alloy powder and induced in situ reactions using a high-energy laser beam, the thermal conductivity and resistance of titanium alloys are improved by induced by self-lubricating and self-lubricating tungsten copper phases. Grinding performance.
It significantly reduces the wear rate of titanium alloy sliding bearings, improves thermal conductivity, and enhances the performance of bearings in high temperature environments.
Smart Images

Figure CN119433285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a titanium alloy, in particular to a high-thermal-conductivity self-lubricating titanium alloy for a sliding bearing and a preparation method thereof. Background Art
[0002] Sliding bearings are a type of parts that directly support the journal with a bushing, bear the load and keep the shaft in the normal working position. Compared with rolling bearings, sliding bearings have smaller radial dimensions, simpler structures, and larger load-bearing capacity. They can ensure high manufacturing and operating accuracy while keeping the mechanical structure compact and the volume small. With the rapid development of technologies such as aerospace, aviation, and special vehicles, the requirements for the bearing capacity and wear resistance of sliding bearings at high temperatures are getting higher and higher. Traditional sliding bearings are widely used in heavy-load, low-speed industrial environments, but due to wear and failure caused by poor lubricity, it is difficult for bearings to ensure high stiffness, high strength, and wear resistance in high-temperature environments.
[0003] TiAl alloys are widely used in high-temperature alloy structural components due to their advantages such as high high-temperature strength, low density, creep resistance, and oxidation resistance. However, due to their defects such as high friction coefficient and poor wear resistance, their application areas are greatly limited. TiAl alloy composites with different solid lubrication can be designed to improve their wear resistance. For example, graphene and graphene / Ti3SiC2 reinforced TiAl composites prepared by spark plasma sintering have a friction coefficient of about 0.37 and a wear rate of 2.35×10 -4 mm 3 ·N -1 ·m -1 Ag / Ti3SiC2 reinforced TiAl composites were also prepared by spark plasma sintering, and their friction coefficients were 0.32-0.43 and their wear rates were 1.23-4.13×10 -4 mm 3 ·N -1 ·m -1 The wear rate of the hot-pressed sintered CaF2-BaF2-doped TiAl-based self-lubricating bearing is optimally reduced to 0.56×10 -4 mm 3 ·N -1 ·m -1 The above measures have improved the wear resistance of TiAl alloy sliding bearings to a certain extent. However, the doping of a single solid self-lubricating phase still has the problem of high wear rate. The main reason is that the frictional heat generated during the operation of the sliding bearing will cause the contact surface temperature to rise, which aggravates the severity of bearing wear and leads to more serious bearing wear. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a high thermal conductivity self-lubricating titanium alloy for sliding bearings with improved thermal conductivity and wear resistance.
[0005] Another object of the present invention is to provide a method for preparing a high thermal conductivity self-lubricating titanium alloy for sliding bearings with improved thermal conductivity and wear resistance.
[0006] Technical solution: The high thermal conductivity self-lubricating titanium alloy for sliding bearings described in the present invention includes a substrate, on which there are tungsten-copper phases for improving the thermal conductivity of the titanium alloy and Ti3AlC2 and Ti2AlN with self-lubricating function, and the Ti3AlC2 and Ti2AlN are both formed by in-situ reaction.
[0007] Preferably, the Ti3AlC2 phase is formed by a high-temperature in-situ reaction between TiAl alloy powder and a TiAlC coating deposited on its surface under the action of a high-energy laser beam.
[0008] Preferably, the Ti2AlN phase is formed by a high-temperature in-situ reaction between TiAl alloy powder and a TiAlN coating deposited on the surface thereof under the action of a high-energy laser beam.
[0009] The method for preparing the high thermal conductivity self-lubricating titanium alloy for sliding bearings of the present invention comprises the following steps:
[0010] (1) taking two portions of TiAl alloy powder, depositing TiAlC and TiAlN coatings on the surfaces of the TiAl alloy powders respectively by physical vapor deposition process, and mixing the two portions of TiAl alloy powders on which the TiAlC and TiAlN coatings were deposited respectively to obtain mixed powder;
[0011] (2) ball milling the mixed powder described in step (1), the tungsten-copper alloy powder and the TiAl alloy powder to obtain a TiAl alloy composite material powder;
[0012] (3) A high-energy laser beam is used to perform high-temperature scanning on the TiAl alloy composite material powder in step (2), so as to form Ti3AlC2 and Ti2AlN phases with self-lubricating function and a high thermal conductivity tungsten copper phase on the substrate, thereby obtaining a high thermal conductivity self-lubricating titanium alloy.
[0013] Preferably, the mass ratio of the two portions of TiAl alloy powder in step (1) is 2:1 to 1:2, more preferably 1:2.
[0014] Preferably, the coating thickness in step (1) is 1 to 5 μm, more preferably 1 μm.
[0015] Preferably, in the step (2), the mass ratio of the mixed powder, the tungsten-copper alloy powder and the TiAl alloy powder is 5:5:90 to 8:9:80, more preferably 8:9:80.
[0016] Preferably, the scanning power of the high energy laser beam in step (3) is 250-350W, more preferably 250W.
[0017] Principle of the invention: The present invention is aimed at the material design and manufacturing of high-performance titanium alloy sliding bearings. Aiming at the problem of high wear rate of current TiAl alloy sliding bearings, based on the physical properties of TiAl alloy and thermal analysis during friction, and in accordance with the principles of materials science, a TiAl alloy / tungsten copper alloy composite material system with TiAlC and TiAlN coatings deposited on the surface at room temperature is designed. With the help of the high temperature effect of the high-energy laser beam, an in-situ reaction between Ti-Al-N and Ti-Al-C is induced to form Ti3AlC2 and Ti2AlN with self-lubricating function on the matrix, which act as solid self-lubricating components during friction, thereby reducing the wear rate; at the same time, the solubility between the tungsten copper alloy with high thermal conductivity and the TiAl alloy matrix is low, which enables it to maintain a high thermal conductivity, reduce the friction heat and temperature during friction, effectively reduce the degree of wear, and significantly reduce the wear rate of titanium alloy sliding bearings.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0019] (1) This method uses physical vapor deposition technology to deposit TiAlC and TiAlN coatings on the surface of TiAl alloy powder at room temperature. Under the action of a high-energy laser beam, high temperature induces an in-situ reaction between Ti-Al-N and Ti-Al-C to form layered Ti3AlC2 and Ti2AlN anti-friction phases with self-lubricating function, which can effectively reduce the wear rate of TiAl alloy sliding bearings.
[0020] (2) This method is based on the interaction between the low thermal conductivity of TiAl alloy itself and its wear performance. It uses tungsten-copper alloy with low solubility in TiAl alloy as a thermal conductivity strengthening phase to increase the thermal conductivity of titanium alloy to 2 to 3 times that of existing titanium alloys, enabling it to fully dissipate heat during friction, reduce friction temperature, and thus reduce wear rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a microstructure diagram of the titanium alloy obtained in Example 1;
[0022] Figure 2 It is a comparison chart of the friction coefficients of the titanium alloys obtained in Examples 1-3 and Comparative Examples 1-3;
[0023] Figure 3 It is a comparison chart of the wear rates of the titanium alloys prepared in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below in conjunction with embodiments.
[0025] Example 1
[0026] The high thermal conductivity self-lubricating titanium alloy for sliding bearings of the present invention comprises a substrate on which are formed Ti3AlC2, Ti2AlN and tungsten copper phases with self-lubricating function through in-situ reaction.
[0027] The high thermal conductivity self-lubricating titanium alloy for sliding bearings of the present invention comprises the following steps:
[0028] (1) taking two parts of TiAl alloy powder with a mass ratio of 2:1, using a physical vapor deposition process to deposit 1 μm TiAlC and TiAlN coatings on the surface of the TiAl alloy powders, respectively, and mixing the two parts of TiAl alloy powders deposited with the TiAlC and TiAlN coatings to obtain a mixed powder;
[0029] (2) ball milling the mixed powder described in step (1), the tungsten-copper alloy powder and the TiAl alloy powder in a mass ratio of 5:5:90 under an inert argon protection environment to obtain a TiAl alloy composite material powder;
[0030] (3) A high-energy laser beam with a scanning power of 250 W is used to perform high-temperature scanning on the TiAl alloy composite material powder in step (2), thereby inducing an in-situ reaction between Ti-Al-N and Ti-Al-C, forming Ti3AlC2 and Ti2AlN phases with self-lubricating function and a high thermal conductivity tungsten copper phase on the titanium aluminum alloy matrix, and obtaining a high thermal conductivity self-lubricating titanium alloy.
[0031] Figure 1 1 is a microstructure diagram of the titanium alloy obtained in Example 1, wherein 1-Ti3AlC2, 2-Ti2AlN, 3-tungsten copper phase. Figure 1 It can be found that the slender lamellar Ti3AlC2, short lamellar Ti2AlN and massive high thermal conductivity tungsten copper phase are dispersed on the titanium aluminum alloy matrix. It can also be found that there are no obvious metallurgical defects between the above three phases and the titanium aluminum alloy matrix, showing good interface bonding performance.
[0032] Test of friction coefficient and wear rate: Under the conditions of 50N positive pressure, GCr15 as friction pair and dry friction, the friction coefficient and wear rate of the prepared titanium alloy were tested with a micro-motion amplitude of 1mm for 60min. The wear rate was measured by a three-dimensional profilometer to measure the three-dimensional profile of the wear scar, and then the wear volume was calculated.
[0033] Thermal conductivity test: A laser flash meter based on the transient method was used to measure the thermal diffusion coefficient and heat capacity of the prepared titanium alloy in an inert argon environment at 500°C. The density of the prepared titanium alloy was measured based on the Archimedean drainage method, and the product of the thermal diffusion coefficient, heat capacity and density was calculated as the thermal conductivity.
[0034] Example 2
[0035] The difference between this embodiment and embodiment 1 is that the mass ratio of the two portions of TiAl alloy powder in step (1) is adjusted to 1:2.
[0036] Example 3
[0037] The difference between this embodiment and embodiment 2 is that in step (2), the mass ratio of the mixed powder, the tungsten-copper alloy powder and the TiAl alloy powder is 8:9:80.
[0038] like Figure 2 As shown, the friction coefficients of the high thermal conductivity self-lubricating titanium alloys obtained in Examples 1-3 are all lower than 0.26. In the prior art, the friction coefficient of the TiAl alloy reinforced with a single layered lubricating phase Ti3SiC2 was measured to be approximately 0.32 under dry friction conditions using a pin-disc friction method (Chen Weidong. Simulation and experimental study on tribological properties of TiAl-based self-lubricating sliding bearings [D]. Yanshan University, 2020.). The friction coefficient of the titanium alloy obtained by this technical scheme is only 80% of that in the prior art, indicating that the in-situ formation of Ti3AlC2 and Ti2AlN self-lubricating phases and the doping of high thermal conductivity tungsten-copper phases effectively reduce the friction coefficient.
[0039] The thermal conductivity test results show that the thermal conductivity of the titanium alloys prepared in Examples 1-3 is between 43.2 and 71.8 W·m -1 ·K -1 It is 2 to 3 times that of the existing single self-lubricating phase reinforced TiAl alloy bearings (Chen Weidong. Simulation and experimental study on tribological properties of TiAl-based self-lubricating sliding bearings [D]. Yanshan University, 2020.).
[0040] like Figure 3 As shown, the wear rate of the high thermal conductivity self-lubricating titanium alloys prepared in Examples 1-3 is no more than 0.6 mm -3 ·N -1 ·m -1 In the prior art, the wear rate of TiAl alloy reinforced with single lamellar lubricating phase Ti3SiC2 is 1.44×10 -5 mm -3 ·N -1 ·m -1(Chen Weidong. Simulation and experimental study on tribological properties of TiAl-based self-lubricating sliding bearings [D]. Yanshan University, 2020.), which is more than twice the wear rate of the titanium alloy obtained by this technical scheme, further illustrating that this method can effectively reduce the friction coefficient and wear rate of titanium alloy.
[0041] Comparative Example 1
[0042] The similarities between this embodiment and embodiment 1 are not repeated here. The difference is that the TiAlC and TiAlN coatings are not deposited on the surface of the TiAl alloy powder in step (1), and only tungsten-copper alloy powder and TiAl alloy powder with a mass ratio of 5:90 are used to directly prepare titanium alloy for sliding bearings using a high-energy laser beam.
[0043] Comparative Example 2
[0044] The similarities between this embodiment and embodiment 1 are not repeated here. The difference is that the TiAlC and TiAlN coatings and tungsten-copper alloy powder are not deposited on the surface of the TiAl alloy powder in steps (1) and (2). Only a single TiAl alloy powder is used to directly prepare the titanium alloy for sliding bearings using a high-energy laser beam.
[0045] Comparative Example 3
[0046] The similarities between this embodiment and embodiment 1 are not repeated here. The difference is that the tungsten-copper alloy powder in step (2) is not used. Instead, only TiAl alloy powder with TiAlC and TiAlN coatings deposited on the surface and TiAl alloy powder are used for ball milling and mixing, and then directly high-energy laser beam forming is used for titanium alloy for sliding bearings.
[0047] According to the experimental results, the titanium alloy prepared in Comparative Example 1 contains only tungsten copper thermal conductive phase, but no Ti3AlC2 and Ti2AlN self-lubricating phase; the titanium alloy prepared in Comparative Example 2 contains neither tungsten copper thermal conductive phase nor Ti3AlC2 and Ti2AlN self-lubricating phase; the titanium alloy prepared in Comparative Example 3 contains only Ti3AlC2 and Ti2AlN self-lubricating phase, but no tungsten copper thermal conductive phase. The friction coefficients of Comparative Examples 1-3 are approximately 0.3, 0.35, and 0.31, respectively, which are more than 16% higher than the friction coefficient of the high thermal conductive self-lubricating titanium alloy prepared by this method. The wear rate of the titanium alloy prepared in Comparative Examples 1-3 is about twice the wear rate of the high thermal conductive self-lubricating titanium alloy prepared by this method. It shows that the doping of the high thermal conductivity tungsten-copper phase in the present application can effectively reduce the friction heat in the friction process of the titanium alloy, reduce the degree of wear in the wear process, and thus improve the wear resistance of the sliding bearing. It further proves that the doping of the self-lubricating phase and the high thermal conductivity phase formed in situ in the present method can significantly improve the wear resistance of the titanium alloy sliding bearing.
Claims
1. A high thermal conductivity self-lubricating titanium alloy for sliding bearings, characterized in that: The invention comprises a substrate, on which there are tungsten copper phase for improving the thermal conductivity of titanium alloy and Ti3AlC2 and Ti2AlN with self-lubricating function, wherein the Ti3AlC2 and Ti2AlN are both formed by in-situ reaction.
2. The high thermal conductivity self-lubricating titanium alloy for sliding bearings according to claim 1, characterized in that: The Ti3AlC2 phase is formed by high-temperature in-situ reaction of TiAl alloy powder and TiAlC coating deposited on the surface thereof under the action of a high-energy laser beam.
3. The high thermal conductivity self-lubricating titanium alloy for sliding bearings according to claim 1, characterized in that: The Ti2AlN phase is formed by high-temperature in-situ reaction of TiAl alloy powder and TiAlN coating deposited on the surface thereof under the action of a high-energy laser beam.
4. A method for preparing the titanium alloy according to claim 1, characterized in that: The following steps are involved: (1) taking two portions of TiAl alloy powder, depositing TiAlC and TiAlN coatings on the surfaces of the TiAl alloy powders respectively by physical vapor deposition process, and mixing the two portions of TiAl alloy powders on which the TiAlC and TiAlN coatings were deposited respectively to obtain mixed powder; (2) ball milling the mixed powder described in step (1), the tungsten-copper alloy powder and the TiAl alloy powder to obtain a TiAl alloy composite material powder; (3) A high-energy laser beam is used to perform high-temperature scanning on the TiAl alloy composite material powder in step (2), so as to form Ti3AlC2 and Ti2AlN phases with self-lubricating function and a high thermal conductivity tungsten copper phase on the substrate, thereby obtaining a high thermal conductivity self-lubricating titanium alloy.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the two portions of TiAl alloy powder in the step (1) is 2:1 to 1:
2.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the two portions of TiAl alloy powder in the step (1) is 1:
2.
7. The preparation method according to claim 4, characterized in that: The coating thickness in step (1) is 1 to 5 μm.
8. The preparation method according to claim 4, characterized in that: In the step (2), the mass ratio of the mixed powder, the tungsten-copper alloy powder and the TiAl alloy powder is 5:5:90 to 8:9:
80.
9. The preparation method according to claim 4, characterized in that: In the step (2), the mass ratio of the mixed powder, the tungsten-copper alloy powder and the TiAl alloy powder is 8:9:
80.
10. The preparation method according to claim 4, characterized in that: In the step (3), the scanning power of the high energy laser beam is 250 to 350 W.